Author Correction: A comparison of tools for the simulation of genomic next-generation sequencing data. Issue 11 (November 2018) - Escalona, Merly; Rocha, Sara; Posada, David
The originally published article contained errors in Fig. 1 (Decision tree for the selection of a suitable NGS genomic simulator), whereby the labels 'Variants' and 'No Variants' had been switched. The correct figure is presented in this notice.